Systematic rare Earth doping to adopt an R32 type huntite structure in NdSc3(BO3)4 crystals - Kuznetsov, Artem B.; Kokh, Konstantin A.; Kaneva, Ekaterina V.; Jamous, Ammar Y.; Svetlichnyi, Valerii A.; Kononova, Nadezda G.; Shevchenko, Vyacheslav S.; Goreyavcheva, Anastasia A.; Kokh, Alexander E. (Dalton transactions)
This study is focused on determining the type and quantity of REE impurities responsible for converting the structure of NdSc3(BO3)4 into an R32 polymorph. According to the single crystal X-ray diffraction of RxNdyScz(BO3)4 (R = Sm-Lu, x + y + z = 4) the samples probably contain several polymorphic modifications. However, the predominant structure has been defined as R32 for R = Eu, Er, Tm, and Yb and P3221 for R = Sm, Gd, Tb, Dy, and Ho. Another potential limitation to the future use of the crystals is a compositional zoning found in the crystals with significant substitution in the scandium position.